2020
DOI: 10.5812/jjm.107453
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Antimicrobial Susceptibility Pattern of Uropathogens in Patients with the Community- and Hospital-Acquired Urinary Tract Infections at a Tertiary Hospital in Somalia

Abstract: Background: Urinary tract infections (UTIs) are the most common infections in the community and in hospitalized patients. Objectives: To investigate the epidemiology and antimicrobial susceptibility pattern of uropathogens and determine the appropriate empirical antibiotics to treat UTIs in the community and hospitalized patients. Methods: A total of 2,485 urine cultures were performed at Mogadishu Somali Turkish Training and Research Hospital. Through the standard Kirby-Bauer disk diffusion method and commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(24 reference statements)
1
8
1
Order By: Relevance
“…Our results showed that the species of the five domi-nant bacteria were consistent with those reported in studies in other regions, including the CHINET for China (5), Zhengzhou (China) (6), Nanjing (China) (26), Seoul (Korea) (27), Somalia (28), and Greece (21), but the proportions of the five dominant bacteria were different. Therefore, it was necessary to analyze the proportions of bacteria in different areas.…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed that the species of the five domi-nant bacteria were consistent with those reported in studies in other regions, including the CHINET for China (5), Zhengzhou (China) (6), Nanjing (China) (26), Seoul (Korea) (27), Somalia (28), and Greece (21), but the proportions of the five dominant bacteria were different. Therefore, it was necessary to analyze the proportions of bacteria in different areas.…”
Section: Discussionsupporting
confidence: 89%
“…The identification of the uropathogens was achieved by a combination of a BD BBL crystal identification system with a series of biochemical tests according to the system of the Clinical and Laboratory Standards Institute (CLSI). The growth of a single uropathogen with >100,000 CFU/mL represents CA-UTI [ 8 ]. The production of extended-spectrum beta-lactamases (ESBL) was identified from positive urine cultures using cephalosporins (ceftriaxone (30 µg), +cefotaxime (30 µg), +ceftazidime (30 µg)) and amoxicillin–clavulanic acid (20/10 µg) as the identifying disc to differentiate the patterns of growth between antibiotics with a lactamase inhibitor and those without.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported that numerous uropathogens are resistant to commonly used antibiotics, which challenges the treatment and empiric therapy of patients with CA-UTI with MDR microorganisms [ 7 ]. Despite the increasing concern relating to antimicrobial-resistant pathogens, the number of UTI patients is increasing swiftly, and the nature of the infection is diverse according to local and geographical locations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study by Mohamed AH regarding epidemiological characteristics and predisposing factors for surgical site infections caused by bacterial pathogens exhibiting multidrug-resistant patterns, epidemiology and antimicrobial susceptibility pattern of uropathogens in patients with the community-and hospital-acquired urinary tract infections at a tertiary hospital in Somalia. It reported higher rates of antimicrobial resistance, multidrug-resistant (MDR), and extensively drug-resistant (XDR) pathogens owing to an improper prescription of antibiotics, epidemic misuse of antimicrobials, self-prescription of antibiotics, and the lack of knowledge about drug resistance [ 14 , 15 ]. This widespread misuse of medications and the availability of the PDE5Is in every community pharmacy in the country became a significant health threat and public health problem.…”
Section: Discussionmentioning
confidence: 99%